KHAZANAH LEKSIKON DALAM RITUAL TEKAO PADA MASYARAKAT DAYAK BAKATIK KAMAYO DI KABUPATEN BENGKAYANG - Karman yarso; Patriantoro Patriantoro; Agus Syahrani (Universitas Tanjungpura, 2019)
Abstract Lexicon of tekao ritual was component of language communication that lotain sense and word usage in language. Tekao was an activity of farming tradition done by BDK community since along time ago. The nice considerod sacret object that has should were be given special meutment through traditional ritual traditions. Tekao ritual contain of sinse that has aspect of culture of the community. So that tekao ritual can be defended, DBK was one of subtribal of Dayak which settle down in Bengkayang Busli regency. The research done in Dusun Ubah Setia Budi Bengkayang district, Bengkayang regency, that was settlement of DBK community. This study was about lexicon form of tekao ritual, lexicon meaning, cultural meaning.The mothode used in this research was descriptive methode with qualitative from. The technique used in this reseach was obsevation, interview, fishing, face to face, note, and record technique, whereas the tool used was guestionnaire and documentation. Based on the result analyst, there one 16 classification in lexicon tekao ritual of DBK community in Bky regency, that is based n ritual lexicon category, cultural thing, tools, foods, drinks, plants, animals, myth, procers, time, place, farming steps, type of soil, rice type, size.Keywords: Lexicon, Tekao ritual, DBK.